PENGARUH MOTIVASI BELAJAR DAN PERSEPSI ATAS METODE PEMBELAJARAN TERHADAP PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL SISWA (Pada SMPN 98 Jakarta Selatan) - Agustina, Teni (www.bsi.ac.id, 2014)
In the process of teaching and learning in schools is very necessary motivation to make students feel excited in Belaja. Needs encouragement or motive to perform certain actions, where it is believed that if the deed has been done, then the equilibrium state was reached and there arose perassan satisfied within the individual. This study aims to determine the extent of the influence on the perception of learning motivation learning method to learning achievement IPS students. These results indicate that there is significant influence learning motivation and perception of the teaching methods together towards achievement of social studies students, a significant difference between achievement motivation toward social studies students and a significant difference between the perceptions of the learning method of learning achievement IPS students. Keywords: Motivation, Perception of Learning Methods and Learning Achievement IPS